Highly-Integrated Hydraulic Smart Actuators and Smart Manifolds for High-Bandwidth Force Control - Barasuol, Victor; Villarreal-Magaña, Octavio A.; Sangiah, Dhinesh; Frigerio, Marco; Baker, Mike; Morgan, Robert; Medrano-Cerda, Gustavo A.; Caldwell, Darwin Gordon; Semini, Claudio (Frontiers in Robotics and AI, 2018)
Hydraulic actuation is the most widely used alternative to electric motors for legged robots and manipulators. It is often selected for its high power density, robustness and high-bandwidth control performance that allows the implementation of force/impedance control. Force control is crucial for robots that are in contact with the environment, since it enables the implementation of active impedance and whole body control that can lead to a better performance in known and unknown environments. This paper presents the hydraulic Integrated Smart Actuator (ISA) developed by Moog in collaboration with IIT, as well as smart manifolds for rotary hydraulic actuators. The ISA consists of an additive-manufactured body containing a hydraulic cylinder, servo valve, pressure/position/load/temperature sensing, overload protection and electronics for control and communication. The ISA v2 and ISA v5 have been specifically designed to fit into the legs of IIT’s hydraulic quadruped robots HyQ and HyQ- REAL, respectively. The key features of these components tackle 3 of today’s main challenges of hydraulic actuation for legged robots through: (1) built-in controllers running inside integrated electronics for high-performance control, (2) low-leakage servo valves for reduced energy losses, and (3) compactness thanks to metal additive manufacturing. The main contributions of this paper are the derivation of the representative dynamic models of these highly integrated hydraulic servo actuators, a control architecture that allows for high-bandwidth force control and their experimental validation with application-specific trajectories and tests. We believe that this is the first work that presents additive-manufactured, highly integrated hydraulic smart actuators for robotics.